Benchmarking laboratory‐scale pomegranate vinegar against commercial wine vinegars: antioxidant activity and chemical composition. (16th May 2018) - Kharchoufi, Samira; Gomez, Juan; Lasanta, Cristina; Castro, Remedios; Sainz, Florencia; Hamdi, Moktar
Abstract: BACKGROUND: There is growing interest in the beneficial health effects of certain fruits, such as pomegranate, and their by‐products, like vinegar. Vinegars contain antioxidant compounds such as polyphenols, which can scavenge free radicals in the body. In this study, the antioxidant properties (2, 2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid and 2, 2‐diphenyl‐1‐picrylhydrazyl scavenging capacities) and global polyphenolic composition of a new functional product, namely a pomegranate vinegar produced in the laboratory from the Gabsi variety, were evaluated and compared with those of commercial wine vinegars (Sherry and Rioja red wine Spanish vinegars). The evolution of the polyphenolic and volatile compositions during production of the pomegranate vinegar was also studied. RESULTS: The results indicate that pomegranate contained a relatively stable total phenolic content that is suitable for the elaboration of vinegar and that this product had an antioxidant capacity comparable to, or even better than, that observed for aged wine vinegars. Regarding the volatiles profile, a high proportion of esters (close to 50%), in relation to alcohols and fatty acids, was observed for pomegranate vinegar, and this is consistent with the high red fruits character identified by sensory analysis. CONCLUSION: Pomegranate vinegar produced in the laboratory has an antioxidant activity and a global phenolic content similar to those of red wine vinegars and higher than most of the white wine vinegars studied. The pomegranate vinegar retained the red fruit sensory character of pomegranate fruit. © 2018 Society of Chemical Industry